Raphaneae report on the 2005 and 2006 survey - Gschwind, Markus 1968-; Ḥasan, Haytham; Grüner, Andreas 1973-; Hübner, Wolfgang (2009)
The exact location and extent of the settlement area of Raphaneae (prov. Hama, Syria) has now been determined through surveys. An integrated discussion of surface finds and historical sources provides a better understanding of the development of the legionary fortress and the Roman to Medieval city.
Ausdehnung von Raphaneae (Prov. Hama, Syrien) festgestellt. Die Analyse der historischen Quellen und der Oberflächenfunde ermöglicht zudem Aussagen zur Entwicklung des Legionslagers und der Stadt von der frühen Kaiserzeit bis in die Kreuzfahrerzeit.
تم تحديد موقع مدينة رفنية (محافظة حماة، سورية) واتساعها بدقة من خلال المسوحات الأثرية. وقد سمحت دراسة المصادر التاريخية واللقى السطحية بالتوصل إلى استنتاجات عن تطور معسكر الفيلق والمدينة من فجر العهد الامبراطوري الروماني وحتى العصور الوسطى.
Keywords: Raphaneae